Hubungan Peran Ayah dengan Orientasi Masa Depan Mahasiswa Semester Akhir Fakultas Psikologi Universitas Negeri Malang - Nande, Sherafie Sharon Sanggalangi; Harsono, Yudi Tri (Flourishing Journal, 2025)
Final year students are students who are in their final semester of study and are working on their final project. In addition to completing academic assignments, final year students also have the challenge of determining careers and interests that can be referred to as future orientation. In terms of structuring the future, a father plays an important role in shaping future orientation. The purpose of this study was to determine whether there is a relationship between the role of the father and the future orientation of final year students of the Faculty of Psychology, State University of Malang. The scale used in this study is the father's role scale and future orientation, which is constructed and has gone through a factor analysis test to obtain evidence of validity based on structure. Hypothesis testing was conducted through correlation tests, resulting in a relationship between the father's role and the future orientation of final-year students at the Faculty of Psychology, Universitas Negeri Malang. Overall, the father's role has a relationship with future orientation, with a correlation coefficient of 0.393 and significance <0.05. Thus, the hypothesis in this study is proven and acceptable. AbstrakMahasiswa tingkat akhir adalah mahasiswa sedang berada pada semester akhir perkuliahan dan sedang mengerjakan tugas akhir. Selain menyelesaikan tugas akademik, mahasiswa tingkat akhir juga memiliki tantangan untuk menentukan karir dan minat, yang dapat disebut sebagai orientasi masa depan. Dalam hal menyusun masa depan, seorang ayah memegang peranan penting dalam menyusun orientasi masa depan. Tujuan dari penelitian ini adalah untuk mengetahui apakah terdapat hubungan antara peran ayah dengan orientasi masa depan mahasiswa tingkat akhir Fakultas Psikologi, Universitas Negeri Malang. Skala yang digunakan dalam penelitian ini adalah skala peran ayah dan orientasi masa depan yang dikonstruk dan telah melalui uji analisis faktor untuk mendapatkan bukti validitas berdasarkan struktur. Uji hipotesis dilakukan melalui uji korelasi dengan hasil terdapat hubungan peran ayah dengan orientasi masa depan mahasiswa tingkat akhir Fakultas Psikologi. Secara keseluruhan, peran ayah memiliki hubungan dengan orientasi masa depan dengan koefisien korelasi sebesar 0.393 dan signifikansi <0.05. Dengan demikian, hipotesis dalam penelitian ini terbukti dan dapat diterima.